A high-fat diet changes placental morphology but does not change biochemical parameters, placental oxidative stress or cytokine levels. (April 2023) - Bondarczuk, Nicole Hiller; Schmidt, Natália Perin; Breyer, Gabriela Merker; de Moura, Ana Carolina; Molz, Patrícia; Barshack, Alethea Gatto; da Motta, Amanda de Souza; Guedes, Renata Padilha; Giovenardi, Márcia
Abstract: Introduction: The placenta is an organ that forms the bridge between mother and fetus during pregnancy. Changes in the intrauterine environment directly impact the fetus' health, with maternal nutrition determining its development. This study analyzed the effects of different diets and probiotic supplementation during pregnancy on the biochemical parameters of maternal serum and placental morphology, oxidative stress, and cytokine levels in mice. Methods: Female mice were fed standard (CONT), restrictive (RD), or high-fat (HFD) diets before and during pregnancy. During pregnancy, the CONT and HFD groups were divided into two groups that received the Lactobacillus rhamnosus LB1.5 three times per week (CONT + PROB and HFD + PROB). The RD, CONT, or HFD groups received vehicle control. Maternal serum biochemical parameters (glucose, cholesterol, and triglycerides) were evaluated. The morphology, redox profile (thiobarbituric acid reactive substances, sulfhydryls, catalase, and superoxide dismutase enzyme activity), and inflammatory cytokines (interleukins 1α, 1β, IL-6, and tumor necrosis factor-alpha) were evaluated in the placenta. Results: The serum biochemical parameters presented no differences between the groups. Regarding placental morphology, the HFD group showed an increased thickness of the labyrinth zone compared to the CONT + PROB group. However, no significant difference was found in the analysis of the placental redox profile and cytokine levels. Discussion: RD and HFD, for 16 weeks before and during pregnancy, as well as probiotic supplementation during pregnancy, caused no change in serum biochemical parameters nor the gestational viability rate, placental redox state, and cytokine levels. However, HFD increased the thickness of the placental labyrinth zone. Highlights: High-fat diet increases the thickness of the labyrinth zone in the placenta. Increased thickness of the placenta may alter transport between mother and fetus. High-fat and restrictive diets during pregnancy did not alter the placental cytokines. Gestational viability was not affected by high-fat or restrictive diets. High-fat and restrictive diets did not alter the redox state in the placenta.